2006
DOI: 10.1002/app.24755
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water‐insoluble functional copolymers containing amide, amine, and carboxylic acid groups and their metal‐ion‐uptake properties

Abstract: The crosslinked poly[N-(3-dimethylamino)-propylmethacrylamide] [P(NDAPA)] and poly [N-(3-dimethylamino)propylmethacrylamide-co-acrylic acid] [P(NDA-PA-co-AA)] were synthesized by radical polymerization. The resins were completely insoluble in water. The metalion-uptake properties were studied by a batch equilibrium procedure for the following metal ions: silver(I), copper(II), cadmium(II), zinc(II), lead(II), mercury(II), chromium(III), and aluminum(III). The P(NDAPA-co-AA) resin showed a lower metal-ion affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It is expected that as the temperature rises, the increase of random motion of ions promotes diffusion of metal ions and probably also the interaction with active sites. However, it is observed that temperature does not affect significantly the ion retention, and all metal ions keep the same retention between 20 and 35°C, similar tendencies have been observed in other similar polymeric matrix studied by our group [18]. In case of time effect, it is possible observe that retention does not change from 15 min of contact until 2 h, suggesting that interaction occurs in the early minutes of contact reaching the highest retention.…”
Section: Selectivity Of the Resinssupporting
confidence: 82%
See 1 more Smart Citation
“…It is expected that as the temperature rises, the increase of random motion of ions promotes diffusion of metal ions and probably also the interaction with active sites. However, it is observed that temperature does not affect significantly the ion retention, and all metal ions keep the same retention between 20 and 35°C, similar tendencies have been observed in other similar polymeric matrix studied by our group [18]. In case of time effect, it is possible observe that retention does not change from 15 min of contact until 2 h, suggesting that interaction occurs in the early minutes of contact reaching the highest retention.…”
Section: Selectivity Of the Resinssupporting
confidence: 82%
“…The phosphonic group is responsible of recognition mechanism, while the sulfonic group is responsible of accessibility of metal ions into resin [11,12]. Several enhancements have been carried out, incorporating new functionalities by modification of resins beads, synthesizing new monomer, or combination of monomers [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Various polymer-based systems for mercury removal have been developed, which are mainly based on new synthetic polymers [8,12,19], modified natural polymers [1,2,5], colloidal systems fabricated from or modified by polymers [13,18,22,23]. Therefore, all hitherto reported systems require chemical synthesis or chemical modification to prepare desired mercury adsorbents.…”
Section: General Remarks Scope and Limitationsmentioning
confidence: 99%
“…In contrast to the styrene‐based resins, these resins are highly hydrophilic, and the water absorption can be controlled by the crosslinker degree and the hydrophilicity of the monomer. Rivas et al have studied several vinyl monomers as homopolymers and copolymers …”
Section: Water‐insoluble Polymersmentioning
confidence: 99%